2008
DOI: 10.1615/critreveukargeneexpr.v18.i3.20
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor Complex and the Control of Gene Expression

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that controls the expression of a diverse set of genes. The toxicity of the potent AhR ligand 2,3,7,8-tetrachlorodibenzop-dioxin is almost exclusively mediated through this receptor. However, the key alterations in gene expression that mediate toxicity are poorly understood. It has been established through characterization of AhR-null mice that the AhR has a required physiological function, yet how endogenous mediators regulate this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
594
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 647 publications
(606 citation statements)
references
References 330 publications
6
594
1
5
Order By: Relevance
“…Importantly, it was clear that the expected genes, CYP1A, UGT1B for BAP and vitellogenin, choriogenin for E2 were highly elevated (Fig 4). In addition glutathione reductase and GSTA showed very similar treatment-response profiles to CYP1A, indicating that in flounder these genes are likely to be regulated by the same mechanism as CYP1A, by the aryl hydrocarbon receptor (Beischlag et al, 2008). This demonstrates that although these genes were not induced by sediment exposure at environmentally relevant concentrations, the systems which regulate them in response to contaminants were intact in the isolated hepatocytes.…”
Section: Discussionmentioning
confidence: 83%
“…Importantly, it was clear that the expected genes, CYP1A, UGT1B for BAP and vitellogenin, choriogenin for E2 were highly elevated (Fig 4). In addition glutathione reductase and GSTA showed very similar treatment-response profiles to CYP1A, indicating that in flounder these genes are likely to be regulated by the same mechanism as CYP1A, by the aryl hydrocarbon receptor (Beischlag et al, 2008). This demonstrates that although these genes were not induced by sediment exposure at environmentally relevant concentrations, the systems which regulate them in response to contaminants were intact in the isolated hepatocytes.…”
Section: Discussionmentioning
confidence: 83%
“…Ligand affinity is not the only factor that controls sensitivity, however. There are several other “control points” in the AHR signaling cascade that can influence the sensitivity to or magnitude of response (Beischlag, Luis Morales, Hollingshead, & Perdew, 2008; Hahn, 1998b). Similarly, the AHR is not the only factor that influences sensitivity to effects of DLCs; the expression and function of other members of the AHR pathway, including ARNT (Nukaya, Walisser, et al., 2010; Tomita, Sinal, Yim, & Gonzalez, 2000; Walisser et al., 2004) and AIP (Nukaya, Lin, et al., 2010), also are important.…”
Section: Ahr Pathwaymentioning
confidence: 99%
“…However, upon binding the ligand, AhR translocates from the cytoplasm to the nucleus, where it interacts with specific DNA response elements in target gene pro- moters and activates gene transcription (43,44). Thus in these studies, we first confirmed that B[a]P treatment results in the redistribution of AhR from the cytoplasm to the nucleus (supplemental Fig.…”
Section: Ahr Activates Transcription Of Abcb6 By Binding To the Ahrementioning
confidence: 99%